Adaptive immune responses to Kaposi's sarcoma-associated herpesvirus. (August 2022) - Nalwoga, Angela; Whitby, Denise
Abstract : Kaposi's sarcoma-associated herpesvirus (KSHV) is a gammaherpesvirus that causes Kaposi's sarcoma (KS), primary effusion lymphoma, multicentric Castleman's disease and KSHV-induced cytokine syndrome. KSHV established lifelong infection and has evolved numerous ways in which to evade adaptive immune responses. Most KSHV infections are asymptomatic but when disease occurs it does so in the context of immune suppression especially HIV infection. It is important therefore to study immune responses to KSHV in order to understand KSHV-related disease pathogenesis. Highlights: T cell responses to KSHV are diverse and weak compared to other herpesviruses. CD8 + T cells in KS tumours are localised to regions that are KSHV LANA negative. Maternal KSHV-specific antibody transfer during pregnancy may protect infants from infection.